Constructing Ion‐Selective Coating Layer with Lithium Ion Conductor LLZO and Binder Li‐Nafion for Separator Used in Lithium‐Sulfur Batteries. Issue 14 (18th July 2022) - Huang, Boyang; Hua, Haiming; Lai, Pengbin; Shen, Xiu; Li, Ruiyang; He, Zheng; Zhang, Peng; Zhao, Jinbao
Abstract: In the study of lithium‐sulfur batteries, the shuttle effect of polysulfide ions is widely regarded as the most critical factor in the battery performance deterioration. In this article, with the strategy of ion‐selection, a method of preparing a coating layer with solid‐phase conduction for a separator was used to suppress such an effect. The coating layer was based on calcined ceramic Li7 La3 Zr2 O12 (LLZO) and formed through a simple coating method to be thin but dense. The gap between particles was filled with lithiated Nafion (Li‐Nafion) which could block polysulfide ions through coulombic interactions of sulfonate groups and allowed the lithium ion conduction. The properties of compactness and the ion‐selection formed a double barrier effect, manifested as the fact that the estimated lithium ion transport number achieved 0.79. Correspondingly, the lithium‐sulfur batteries assembled with the ion‐selective conduction separators had better lithium deposition behavior and exhibit brilliant cycling performances and capacity retention. Abstract : Shuttle effect suppression : The strategy of constructing a single‐ion conductive layer on the separator was used to suppress the shuttle effect of polysulfides. By a simple coating method, a dense and ion‐selective layer was prepared with LLZO and Li‐Nafion. Correspondingly, the lithium ion transport number achieves 0.79, and the lithium‐sulfur batteries had improved lithium deposition behavior and cycling performances.